5-5-5-5-5-5*-6=8xy

Simple and best practice solution for 5-5-5-5-5-5*-6=8xy equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-5-5-5-5-5*-6=8xy equation:


Simplifying
5 + -5 + -5 + -5 + -5 + -5 * -6 = 8xy

Multiply -5 * -6
5 + -5 + -5 + -5 + -5 + 30 = 8xy

Combine like terms: 5 + -5 = 0
0 + -5 + -5 + -5 + 30 = 8xy
-5 + -5 + -5 + 30 = 8xy

Combine like terms: -5 + -5 = -10
-10 + -5 + 30 = 8xy

Combine like terms: -10 + -5 = -15
-15 + 30 = 8xy

Combine like terms: -15 + 30 = 15
15 = 8xy

Solving
15 = 8xy

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8xy' to each side of the equation.
15 + -8xy = 8xy + -8xy

Combine like terms: 8xy + -8xy = 0
15 + -8xy = 0

Add '-15' to each side of the equation.
15 + -15 + -8xy = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -8xy = 0 + -15
-8xy = 0 + -15

Combine like terms: 0 + -15 = -15
-8xy = -15

Divide each side by '-8y'.
x = 1.875y-1

Simplifying
x = 1.875y-1

See similar equations:

| 2p-11=-41+8p | | 11-16-a= | | 2v+3-4v=-1(v+9) | | 2p-24=18+9p | | -15u^2v^2+25u^2v-40uv^2= | | 5x^3+x^2-24x-13=36 | | 3y=-2x+7 | | X*x-121=8 | | 3(-3x-1)=-8(x-1) | | (a+5)-(a+3)= | | 3+5z+z^2=0 | | 6s+5=3s+26 | | 2x*4y=4b | | -3(3b+2)+(10b-8)=0 | | 2-3q=-4 | | -4y-16=-y-4 | | (25b-3)-6(4b+3)=-7 | | -47-16=-y-4 | | x^2+3=10x+4x^2 | | x^2+3=10 | | 5x-(4x+5)=3 | | 9y+2=-2 | | -5x+36=-x | | -5x+36=-6 | | 6u=3u-6 | | 7x+4x+2+6=3x+3+7x | | -4x+5y=25 | | -8v-35=0 | | 6n=2.4 | | 0=7y+6 | | 729=z(z-16) | | 2k-4=6 |

Equations solver categories